MANIFESTATIONS OF PATIENCE IN WINSTON GROOM’S FORREST GUMP: A LITERARY PSYCHOLOGICAL STUDY BASED ON SZUTTA’S MODEL - Pardi, Pardi; Hartika, Tri (Universitas Islam Sumatera Utara, 2025)
This study examines the manifestation of patience as a moral virtue in Winston Groom's novel Forrest Gump through Szutta's (2020) theoretical framework of patience competence. Using qualitative methodology with descriptive analysis, this research investigates how the protagonist exemplifies patience through two core characteristics: perseverance and sincerity. The findings reveal that Forrest's perseverance manifests as sustained determination in overcoming life challenges, particularly evidenced in his shrimp business venture where he persists despite initial failures. Simultaneously, his sincerity appears through selfless actions and unconditional assistance without expectation of reward. The analysis demonstrates that patience in Forrest Gump represents not passive endurance but active competence - a strategic virtue enabling him to navigate bullying, personal loss, and social prejudice while maintaining moral integrity. The integration of perseverance and sincerity transforms his perceived intellectual limitations into extraordinary resilience, positioning patience as a transformative force in human experience. This study contributes to literary psychology by illustrating how virtue theory can illuminate character development while affirming literature's capacity to reflect complex psychological realities.